Tuning Butyrylcholinesterase Inactivation and Reactivation by Polymer‐Based Protein Engineering - Zhang, Libin (Adv Sci (Weinh), 2019)
Organophosphate nerve agents rapidly inhibit cholinesterases thereby destroying the ability to sustain life. Strong nucleophiles, such as oximes, have been used as therapeutic reactivators of cholinesterase‐organophosphate complexes, but suffer from short half‐lives and limited efficacy across the broad spectrum of organophosphate nerve agents. Cholinesterases have been used as long‐lived therapeutic bioscavengers for unreacted organophosphates with limited success because they react with organophosphate nerve agents with one‐to‐one stoichiometries. The chemical power of nucleophilic reactivators is coupled to long‐lived bioscavengers by designing and synthesizing cholinesterase‐polymer‐oxime conjugates using atom transfer radical polymerization and azide‐alkyne “click” chemistry. Detailed kinetic studies show that butyrylcholinesterase‐polymer‐oxime activity is dependent on the electrostatic properties of the polymers and the amount of oxime within the conjugate. The covalent coupling of oxime‐containing polymers to the surface of butyrylcholinesterase slows the rate of inactivation of paraoxon, a model nerve agent. Furthermore, when the enzyme is covalently inhibited by paraoxon, the covalently attached oxime induced inter‐ and intramolecular reactivation. Intramolecular reactivation will open the door to the generation of a new class of nerve agent scavengers that couple the speed and selectivity of biology to the ruggedness and simplicity of synthetic chemicals.